Nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double-heterojunction composite photocatalyst and preparation method thereof
Through the graphite-like carbon nitride biheterojunction composite photocatalyst doped with nickel sulfide/cadmium sulfide/sulfur, the nanosheet-like structure self-assembled by NiS/CdS and S-g-C3N4, the existing photocatalyst is solved by self-assembly of NiS/CdS and S-g-C3N4. The problem has significantly improved the activity and performance of photocatalytic hydrogen evolution.
Patent Information
- Application Number
- CN202411374755.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-29
AI Technical Summary
The photocatalytic efficiency of existing photocatalysts such as pure g-C3N4 is limited, and the photocatalytic hydrogen evolution performance cannot be significantly improved after loading the cocatalyst. The bandwidth of titanium dioxide can only use 4% ultraviolet light of the solar spectrum, which cannot meet the needs of Industrial application requirements.
Using graphite-like phase carbon nitride dual heterojunction composite photocatalyst doped with nickel sulfide/cadmium sulfide/sulfur, a three-dimensional structure is formed by self-assembly of NiS/CdS and S-g-C3N4, and uniformly loaded at S-g-C3N4. At present, CTAB and polypyrrole are used to adjust the morphology and conductivity to enhance photocatalytic activity.
The photocatalytic hydrogen evolution activity of the photocatalyst is significantly improved, the active area and specific surface area are increased, the separation and transmission of photogenerated charges are promoted, and the photocatalytic performance of g-C3N4 is improved.
Smart Images

Figure CN119140148A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysis, and in particular relates to a nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst and a preparation method thereof. Background Art
[0002] Solar energy is an inexhaustible energy source, which is widely used in various forms such as photothermal conversion, solar photovoltaic power generation, and photochemical reactions. In recent years, due to the continuous energy shortage and environmental crisis, the development of environmentally friendly photocatalytic semiconductors has become a hot topic. Therefore, the photochemical utilization of solar energy has emerged and continues to receive more and more attention. This mainly includes three aspects: photocatalytic reduction of CO2, photocatalytic water splitting into H2, and photocatalytic degradation of organic pollutants. Among them, photocatalytic degradation of organic pollutants is of great significance for solving environmental pollution problems. Titanium dioxide (TiO2) is a well-known photocatalytic semiconductor material with a wide bandgap (3.2 eV) and can only utilize ultraviolet light, which accounts for only about 4% of the entire solar spectrum. Therefore, the performance of TiO2 cannot meet the needs of industrial applications of solar energy utilization, so the development of new and efficient photocatalytic systems is still in progress.
[0003] In recent years, graphite-like carbon nitride materials (g-C3N4) have been considered as a new type of metal-free semiconductor material due to their excellent semiconductor properties and suitable band gap (2.69 eV). g-C3N4 exhibits excellent photocatalytic performance in photocatalytic splitting of water for hydrogen evolution and photocatalytic degradation of organic pollutants under visible light. The most commonly used method for preparing g-C3N4 is to directly heat different organic precursors for thermal polycondensation, which is simple to operate and suitable for mass production. At the same time, the precursors for preparing g-C3N4 are mainly dicyandiamide, melamine, urea and thiourea, which are much cheaper than the raw materials for preparing other photocatalysts. However, due to the high recombination rate of photogenerated electron-hole pairs, the photocatalytic efficiency of pure g-C3N4 is still limited. Technicians have adopted a variety of methods to improve the photocatalytic activity of pure g-C3N4 and suppress the electron-hole recombination of g-C3N4 as much as possible.
[0004] Generally, building heterojunctions with other semiconductors is a promising strategy to extend the absorption edge of g-C3N4 into the visible light region and hinder the recombination of photogenerated carriers therein. However, this strategy also has negative effects, such as reducing the redox ability of photogenerated electron-hole pairs. The use of suitable co-catalysts is widely considered to be a promising solution to enhance the photocatalytic hydrogen production ability of g-C3N4, as it provides additional reaction sites and accelerates the photocatalytic surface hydrogen production kinetics. Among these co-catalysts, NiS has received considerable attention due to its high earth abundance of the required elements, low cost, and excellent H2 evolution performance. However, after loading NiS on the surface of g-C3N4, the photocatalytic hydrogen evolution performance of g-C3N4 was not significantly improved. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention aims to provide a nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst and a preparation method thereof, wherein the composite photocatalyst material is composed of NiS / CdS and Sg-C3N4, wherein NiS, CdS and Sg-C3N4 all present a typical nanosheet structure, and the NiS and CdS nanosheets self-assemble into a three-dimensional structure formed by stacking nanosheets, which are uniformly loaded on the Sg-C3N4 nanosheets.
[0006] The present invention is achieved through the following technical solutions: A method for preparing a nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst comprises the following steps: S1, mixing S-doped g-C3N4 nanosheet powder, nickel chloride hexahydrate, cadmium acetate, thioacetamide, hexadecyltrimethylammonium bromide, and polypyrrole in aqueous ammonia, wherein the molar ratio of nickel chloride hexahydrate, cadmium acetate, and thioacetamide is (1-5):(1-6):(2-12), to obtain a precursor solution; S2, heat-treating the precursor solution at 120-180 °C to obtain a reaction solution, washing the precipitate in the reaction solution and drying it to obtain a nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst.
[0007] Preferably, the S-doped g-C3N4 nanosheet powder in S1 is obtained by the following process: Melamine and thiocyanate are dissolved in an ethanol solution at a molar ratio of (1-10):(1-5) to obtain a mixed solution. The mixed solution is then evaporated to dryness and the mixture is calcined at 500-650 °C for 2-6 h under the protection of an inert atmosphere, and finally ground to obtain S-doped g-C3N4 nanosheet powder.
[0008] Furthermore, in the ethanol solution, the volume ratio of ethanol to ultrapure water is (0.1-2):(2-5), and when the mixture is calcined, the temperature is raised from room temperature at a rate of 2-8 °C / min, and after reaching 500-650 °C, it is calcined at 500-650 °C for 2-6 h.
[0009] Preferably, in S1, the molar ratio of hexadecyltrimethylammonium bromide, polypyrrole and nickel chloride hexahydrate is (1-3):(0.001-0.05):(1-5).
[0010] Preferably, in S1, the mass ratio of nickel chloride hexahydrate to S-doped g-C3N4 nanosheet powder is (0.01-0.5):(1-10).
[0011] Preferably, in S1, the ratio of S-doped g-C3N4 nanosheet powder to ammonia water is (1-10) g:(40-60) mL, and the ammonia water is obtained by diluting analytically pure ammonia water with ultrapure water, and the volume ratio of analytically pure ammonia water to ultrapure water is (1-2):(2-9).
[0012] Preferably, S1 first mixes nickel chloride hexahydrate, cadmium acetate, thioacetamide, hexadecyltrimethylammonium bromide, polypyrrole and S-doped g-C3N4 nanosheet powder, then adds them into ammonia water, stirs for 60-100 min, ultrasonicates for 60-150 min, and finally stirs for 30-60 min to obtain a precursor solution.
[0013] Preferably, S2 heats the precursor solution at 120-180 °C for 4-8 h to obtain a reaction solution.
[0014] Preferably, S2 centrifuges the reaction solution, then washes it with deionized water and anhydrous ethanol for 3-5 times respectively to obtain a precipitate, and then dries the precipitate at 60-80 °C for 12-24 h to obtain a nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst.
[0015] A nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst obtained by the preparation method of the nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst described in any of the above items, wherein cadmium sulfide and nickel sulfide self-assemble into a three-dimensional structure composed of nanosheets and are uniformly loaded on sulfur-doped graphite-like carbon nitride nanosheets.
[0016] Compared with the prior art, the present invention has the following beneficial technical effects: The invention discloses a method for preparing a nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst. Non-metallic element S-doped -g-C3N4 can effectively optimize the energy band structure of carbon nitride, thereby effectively improving the hydrogen evolution activity of the photocatalyst. Then, a one-step hydrothermal method is adopted to prepare the catalyst in ammonia water at 120-180 °C. CTAB is a surfactant, which can enhance the interface interaction between NiS and CdS and Sg-C3N4 respectively. The unique long-chain structure of CTAB can well play a role in morphology regulation, effectively avoid the agglomeration of NiS and CdS, and effectively increase the active area. Polypyrrole can enhance the intrinsic conductivity of NiS / CdS / Sg-C3N4 on the one hand, and on the other hand, it can enhance the heterojunction by complexing NiS and CdS through its own structure. The alkaline solution can adjust the pH of the precursor solution. The weak alkalinity will not destroy the structure of Sg-C3N4 itself, and it plays a certain protective role. At the same time, the gas generated by the decomposition of ammonia water can effectively adjust the morphology of the composite material during the hydrothermal reaction and promote the formation of multi-dimensional morphology. The conditions are simple and easy to control, and the production cost is low. A composite material with a double heterogeneous structure is obtained. The one-step synthesis makes it have a good heterogeneous interface, and its structure can greatly promote the photogenerated charge separation efficiency of the catalyst. CdS and NiS self-assemble into a three-dimensional structure composed of nanosheets, which are uniformly loaded on the Sg-C3N4 nanosheets to form a three-dimensional nanosheet stacking structure. This structure can be used to enhance the specific surface area of the NiS / CdS / Sg-C3N4 composite photocatalyst, effectively promote the separation and transmission of photogenerated charges, and the double heterogeneous interface provides a fast charge transfer pathway for the rapid migration of electrons and holes in the catalytic process, thereby achieving the goal of accelerating the separation of photogenerated charges, and ultimately significantly improving the photocatalytic hydrogen evolution activity of g-C3N4.
[0017] Furthermore, the solid-phase sintering method can obtain porous S-doped g-C3N4 porous nanosheets, which can effectively increase their specific surface area and active sites during the photocatalytic hydrogen evolution reaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is the X-ray diffraction analysis diagram of NiS / CdS / Sg-C3N4 prepared in Example 1 of the present invention.
[0019] Figure 2 This is a scanning image of NiS / CdS / Sg-C3N4 prepared in Example 1 of the present invention at 1 μm.
[0020] Figure 3 This is the TEM image of NiS / CdS / Sg-C3N4 prepared in Example 1 of the present invention at 20 nm.
[0021] Figure 4This is a graph showing the hydrogen evolution performance of Sg-C3N4, CdS / Sg-C3N4 and NiS / CdS / Sg-C3N4 prepared in Example 1 of the present invention under visible light within four hours. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.
[0023] The present invention discloses a method for preparing a nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst, comprising the following steps: Step 1, obtaining S-doped g-C3N4 nanosheets by one-step calcination in a tube furnace.
[0024] First, the precursor was prepared by the oil bath method, and the specific operation was as follows: Melamine and thiocyanuric acid are placed in a beaker containing an ethanol solution in a molar ratio of (1-10):(1-5), wherein the volume ratio of anhydrous ethanol to ultrapure water is (0.1-2):(2-5), and then stirred for 2-6 hours. Finally, the mixed solution is placed in an oil bath and heated at a temperature of 90-120 °C. After the solution is completely evaporated, a mixed solid A can be obtained; Step 2, spreading solid A in a porcelain boat, calcining in a tube furnace under the protection of an inert atmosphere, the calcination temperature is 500-650 ° C, the holding time is 2-6 h, and the temperature is raised from room temperature at a rate of 2-8 ° C / min. S is doped in the process of forming carbon nitride. 500-650 ° C can ensure that melamine and thiocyanate can be completely polymerized, thereby ensuring the successful preparation of S-doped carbon nitride; Step 3, after calcination, the sample is naturally cooled in the furnace and ground in a mortar for 40-120 min to obtain yellow powder B, i.e., flake S-doped g-C3N4; Step 4, nickel chloride hexahydrate, cadmium acetate, thioacetamide, hexadecyltrimethylammonium bromide (CTAB) and polypyrrole are prepared in a molar ratio of (1-5):(1-6):(2-12):(1-3):(0.001-0.05), and then powder B is added for mixing, wherein the mass ratio of nickel chloride hexahydrate to powder B is (0.01-0.5):(1-10), and then 40-60 mL of ammonia water (corresponding to 1 g of powder B) is added, which is obtained by diluting analytically pure ammonia water with ultrapure water, wherein the volume ratio of ammonia water (AR) to ultrapure water is (1-2):(2-9). First, stir on a magnetic stirrer for 60-100 min, then ultrasonicate for 60-150 min, and finally stir for 30-60 min, and then quickly pour the mixture into the liner of a 100 mL reactor; Step 5, set the working temperature of the oven to 120-180 ° C, wait for the temperature in the oven to rise to the set temperature, then put the sealed reactor into the oven, keep warm for 4-8 h, CTAB as a surfactant can enhance the interface interaction between NiS and CdS and Sg-C3N4, the unique long-chain structure of CTAB can play a good role in morphology regulation, effectively avoid the agglomeration of NiS and CdS, and effectively increase the active area. On the one hand, polypyrrole can enhance the intrinsic conductivity of NiS / CdS / Sg-C3N4, and on the other hand, it can enhance the heterojunction by complexing NiS and CdS through its own structure. Alkaline solution can adjust pH, weak alkalinity will not destroy the structure of Sg-C3N4 itself, and play a certain protective role. At the same time, the gas generated by the decomposition of ammonia water can effectively regulate the morphology of the composite material during the hydrothermal reaction and promote the formation of multidimensional morphology. After the temperature in the oven drops to room temperature, take out the reactor and cool it down. The cooled reaction solution was poured out and centrifuged, and washed with deionized water and anhydrous ethanol for 3-5 times respectively to obtain a precipitate, which was then placed in an oven and dried at 60-80 °C for 12-24 h to obtain solid C, i.e., NiS / CdS / Sg-C3N4 photocatalyst.
[0025] Embodiment 1: The present invention discloses a method for preparing a nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst, comprising the following steps: Step 1, S-doped g-C3N4 nanosheets can be obtained by one-step calcination in a tubular furnace. First, the precursor is prepared by an oil bath method. The specific operation is as follows: melamine and thiocyanate are placed in a beaker containing an ethanol solution in a molar ratio of 8:3, wherein the volume ratio of anhydrous ethanol to ultrapure water is 1:4, and then stirred for 5 hours. Finally, the mixed solution is placed in an oil bath pot and heated. The heating temperature is 100 ° C. After the solution is completely evaporated, solid A can be obtained; Step 2, spread solid A in a porcelain boat, and calcine in a tube furnace under the protection of an inert atmosphere, the calcination temperature is 500 ° C, the holding time is 6 h, and the heating rate is 5 ° C / min; Step 3, after calcination, the sample is naturally cooled in the furnace and ground in a mortar for 60 min to obtain yellow powder B, i.e., flake S-doped g-C3N4; Step 4, nickel chloride hexahydrate, cadmium acetate, thioacetamide, hexadecyltrimethylammonium bromide (CTAB) and polypyrrole are prepared in a molar ratio of 2:3:5:1:0.01, and then powder B is added for mixing, wherein the mass ratio of nickel chloride hexahydrate to powder B is 0.02:5, and then 50 mL of ammonia water (corresponding to 1g of powder B) is added, wherein the volume ratio of ammonia water (AR) to ultrapure water is 1:9. First, stir on a magnetic stirrer for 90 min, then ultrasonicate for 60 min, and finally stir for 30 min, and then quickly pour the mixture into the liner of a 100 mL reactor; Step 5, set the working temperature of the oven to 140 °C, wait until the temperature in the oven rises to the set temperature, then put the sealed reactor into the oven, keep it warm for 5 hours, and take out the reactor to cool after the temperature in the oven drops to room temperature. Pour out the cooled reaction solution and centrifuge it, wash it three times with deionized water and anhydrous ethanol respectively to obtain a precipitate, and then put it into an oven at 80 °C to dry for 14 hours to obtain solid C, that is, NiS / CdS / Sg-C3N4 photocatalyst.
[0026] The photocatalytic effect of NiS / CdS / Sg-C3N4 was tested using the LabSolar 6A fully automatic photocatalytic evaluation system (mainly used for photocatalysis, photoelectrocatalysis, electrocatalysis and other reactions). The specific test process is: 30 mg of composite photocatalyst and 15 mL of triethanolamine were weighed, placed in a glass reaction container filled with 85 mL of deionized water, stirred, and illuminated with a 300 W xenon lamp for 4 h.
[0027] Embodiment 2: The present invention discloses a method for preparing a nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst, comprising the following steps: Step 1, S-doped g-C3N4 nanosheets can be obtained by one-step calcination in a tubular furnace. First, the precursor is prepared by an oil bath method. The specific operation is as follows: melamine and thiocyanate are placed in a beaker containing an ethanol solution in a molar ratio of 5:5, wherein the volume ratio of anhydrous ethanol to ultrapure water is 0.5:3, and then stirred for 6 hours. Finally, the mixed solution is placed in an oil bath pot and heated. The heating temperature is 90 ° C. After the solution is completely evaporated, solid A can be obtained; Step 2, spread solid A in a porcelain boat, and calcine in a tube furnace under the protection of an inert atmosphere, the calcination temperature is 550 ° C, the holding time is 4 h, and the heating rate is 5 ° C / min; Step 3, after calcination, the sample is naturally cooled in the furnace and ground in a mortar for 60 min to obtain yellow powder B, i.e., flake S-doped g-C3N4; Step 4, nickel chloride hexahydrate, cadmium acetate, thioacetamide, hexadecyltrimethylammonium bromide (CTAB) and polypyrrole are prepared in a molar ratio of 1:4:5:2:0.02, and then powder B is added for mixing, wherein the mass ratio of nickel chloride hexahydrate to powder B is 0.1:4, and then 60 mL of ammonia water (corresponding to 1g of powder B) is added, wherein the volume ratio of ammonia water (AR) to ultrapure water is 1:8. First, stir on a magnetic stirrer for 60 min, then ultrasonicate for 120 min, and finally stir for another 60 min, and then quickly pour the mixture into the 100 mL reactor liner; Step 5, set the working temperature of the oven to 160 ° C, wait until the temperature in the oven rises to the set temperature, then put the sealed reactor into the oven, keep it warm for 4 hours, and take out the reactor to cool after the temperature in the oven drops to room temperature. Pour out the cooled reaction solution and centrifuge it, wash it with deionized water and anhydrous ethanol for more than three times to obtain a precipitate, and then put it into an oven at 70 ° C to dry for 10 hours to obtain solid C, that is, NiS / CdS / Sg-C3N4 photocatalyst.
[0028] The photocatalytic effect of NiS / CdS / Sg-C3N4 was tested using the LabSolar 6A fully automatic photocatalytic evaluation system. The specific test process is: 30 mg of composite photocatalyst and 15 mL of triethanolamine were weighed, placed in a glass reaction container filled with 85 mL of deionized water, stirred, and illuminated with a 300 W xenon lamp for 4 h.
[0029] Embodiment 3: The present invention discloses a method for preparing a nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst, comprising the following steps: Step 1, S-doped g-C3N4 nanosheets can be obtained by one-step calcination in a tubular furnace. First, the precursor is prepared by an oil bath method. The specific operation is as follows: melamine and thiocyanate are placed in a beaker containing an ethanol solution in a molar ratio of 6:4, wherein the volume ratio of anhydrous ethanol to ultrapure water is 1:5, and then stirred for 4 hours. Finally, the mixed solution is placed in an oil bath pot and heated. The heating temperature is 120 ° C. After the solution is completely evaporated, solid A can be obtained; Step 2, spread solid A in a porcelain boat, and calcine in a tube furnace under the protection of an inert atmosphere, the calcination temperature is 600 ° C, the holding time is 2 h, and the heating rate is 2 ° C / min; Step 3, after calcination, the sample is naturally cooled in the furnace and ground in a mortar for 50 min to obtain yellow powder B, i.e., flake S-doped g-C3N4; Step 4, nickel chloride hexahydrate, cadmium acetate, thioacetamide, hexadecyltrimethylammonium bromide (CTAB) and polypyrrole are prepared in a molar ratio of 2:5:7:3:0.05, and then powder B is added for mixing, wherein the mass ratio of nickel chloride hexahydrate to powder B is 0.3:8, and then 60 mL of ammonia water (corresponding to 1g of powder B) is added, wherein the volume ratio of ammonia water (AR) to ultrapure water is 2:5. First, stir on a magnetic stirrer for 60 min, then ultrasonicate for 120 min, and finally stir for another 60 min, and then quickly pour the mixture into the 100 mL reactor liner; Step 5, set the working temperature of the oven to 150 °C, wait until the temperature in the oven rises to the set temperature, then put the sealed reactor into the oven, keep it warm for 6 hours, and take out the reactor to cool after the temperature in the oven drops to room temperature. Pour out the cooled reaction solution and centrifuge it, wash it three times with deionized water and anhydrous ethanol respectively to obtain a precipitate, and then put it into an oven at 60 °C to dry for 15 hours to obtain solid C, that is, NiS / CdS / Sg-C3N4 photocatalyst.
[0030] The photocatalytic effect of NiS / CdS / Sg-C3N4 was tested using the LabSolar 6A fully automatic photocatalytic evaluation system. The specific test process is as follows: 30 mg of composite photocatalyst and 15 mL of triethanolamine were weighed and placed in a glass reaction container containing 85 mL of deionized water, and then illuminated with a 300 W xenon lamp for 4 h.
[0031] Figure 1 The horizontal axis is the 2θ angle, and the vertical axis is the diffraction peak intensity. At 27°, they correspond to the (002) crystal plane of g-C3N4, and NiS / CdS / Sg-C3N4 can also accurately correspond to NiS PDF#12-0041 and CdS PDF#41-1049, indicating that NiS / CdS / Sg-C3N4 photocatalysts were successfully prepared.
[0032] Figure 2 In the experiment, NiS, CdS and Sg-C3N4 all showed typical nanosheet structures, among which Sg-C3N4 showed a porous nanosheet structure. NiS and CdS nanosheets also self-assembled into a unique three-dimensional structure composed of nanosheets, which were uniformly loaded on the Sg-C3N4 nanosheets.
[0033] from Figure 3The grain boundaries and phase interfaces inside the NiS / CdS / Sg-C3N4 photocatalyst can be observed. The lattice spacing of 0.186 nm is the (131) crystal plane of NiS, while the lattice spacing of 0.356 nm corresponds to the (100) crystal plane of the CdS species, which is consistent with the XRD results. Therefore, it can be determined that there are a large number of heterogeneous interfaces in the NiS / CdS / Sg-C3N4 photocatalyst, which is of great significance for the exposure of active sites and performance enhancement.
[0034] like Figure 4 As shown, after loading NiS / CdS, the hydrogen evolution activity of Sg-C3N4 has been significantly improved. At the same time, compared with CdS / Sg-C3N4 (no nickel chloride hexahydrate is added in step 4 of Example 1), the hydrogen evolution amount of NiS / CdS / Sg-C3N4 double heterojunction catalyst reaches 2410 µmol / g within four hours.
Claims
1. A method for preparing a nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst, It is characterized in that The following steps are involved: S1, S-doped gC 3 N 4 The nanosheet powder is uniformly mixed with nickel chloride hexahydrate, cadmium acetate, thioacetamide, hexadecyltrimethylammonium bromide and polypyrrole in aqueous ammonia, wherein the molar ratio of nickel chloride hexahydrate, cadmium acetate and thioacetamide is (1-5):(1-6):(2-12) to obtain a precursor solution; S2, heat-treating the precursor solution at 120-180 °C to obtain a reaction solution, washing the precipitate in the reaction solution and drying it to obtain a nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst.
2. The method for preparing the nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst according to claim 1, It is characterized in that S1 S doped gC 3 N 4 Nanosheet powder is obtained by the following process: Melamine and thiocyanate were dissolved in an ethanol solution at a molar ratio of (1-10):(1-5) to obtain a mixed solution, and then the mixture was evaporated to dryness and calcined at 500-650 °C for 2-6 h under the protection of an inert atmosphere, and finally ground to obtain S-doped gC 3 N 4 Nanosheet powder.
3. The method for preparing the nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst according to claim 2, It is characterized in that In the ethanol solution, the volume ratio of ethanol to ultrapure water is (0.1-2):(2-5). When the mixture is calcined, the temperature is raised from room temperature at a rate of 2-8 °C / min, and after reaching 500-650 °C, it is calcined at 500-650 °C for 2-6 h.
4. The method for preparing the nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst according to claim 1, It is characterized in that In S1, the molar ratio of hexadecyltrimethylammonium bromide, polypyrrole and nickel chloride hexahydrate is (1-3):(0.001-0.05):(1-5).
5. The method for preparing the nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst according to claim 1, It is characterized in that In S1, nickel chloride hexahydrate and S-doped gC 3 N 4 The mass ratio of the nanosheet powder is (0.01-0.5):(1-10).
6. The method for preparing the nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst according to claim 1, It is characterized in that In S1, S-doped gC 3 N 4 The ratio of nanosheet powder to ammonia water is (1-10) g: (40-60) mL. The ammonia water is obtained by diluting analytically pure ammonia water with ultrapure water. The volume ratio of analytically pure ammonia water to ultrapure water is (1-2): (2-9).
7. The method for preparing the nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst according to claim 1, It is characterized in that S1 firstly mixed nickel chloride hexahydrate, cadmium acetate, thioacetamide, hexadecyltrimethylammonium bromide, polypyrrole and S-doped gC 3 N 4 The nanosheet powders are mixed, then added into ammonia water, stirred for 60-100 min, ultrasonicated for 60-150 min, and finally stirred for 30-60 min to obtain a precursor solution.
8. The method for preparing the nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst according to claim 1, It is characterized in that S2: heat the precursor solution at 120-180 °C for 4-8 h to obtain a reaction solution.
9. The method for preparing the nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst according to claim 1, It is characterized in that S2 The reaction solution is first centrifuged, and then washed with deionized water and anhydrous ethanol for 3-5 times respectively to obtain a precipitate, and then the precipitate is dried at 60-80 °C for 12-24 h to obtain a nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst.
10. A nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst obtained by the preparation method of the nickel sulfide / cadmium sulfide / sulfur-doped graphite-like carbon nitride double heterojunction composite photocatalyst described in any one of claims 1 to 9.
Citation Information
Patent Citations
g-C3N4 nanosheet / CdS composite visible-light-driven photocatalyst
CN103785434A
Preparation method used for effective construction of Z type ternary heterojunction CdS / NiS / g-C3N4 photocatalyst
CN110280287A
Carbon nitride high-load dispersed NiS photocatalytic degradation material and preparation method thereof
CN113600220A
Graphite-phase carbon nitride photocatalyst for photocatalytic hydrogen production and preparation method thereof
CN114367299A
Process for the biomimetic synthesis of polyaniline compounds and use thereof to manufacture supercapacitors
WO2019098814A1
Cited By
Preparation method and application of highly crystallized cadmium sulfide photocatalyst
CN120305985A
Preparation method and application of zinc cadmium sulfide solid solution photocatalyst
CN120605738A
